Effect of IT affordance in live streaming on trust and purchase intention for jiniso at shopee - Nurhapizah, Siti; Ramadania, Ramadania; Purmono, Bintoro Bagus; Fauzan, Rizky; Yakin, Ikram (Jurnal Ekonomi, 2024)
Live streaming shopping has developed into a unique business model with different features. This study will examine how the IT affordance (visibility, metavoicing, interactivity, guidance shopping, and trading affordance) of live streaming on the Shopee application can affect consumer trust and purchase intention. The data collection methodology employed in this study was the utilization of a questionnaire as the primary instrument for data gathering, with a sample being selected for participation size of 220 respondents. The employed sampling technique was purposive sampling, which involved the utilization of Structural Equation Modeling (SEM) and AMOS statistical tools. The findings of the study indicate that trust is influenced in a favorable and statistically significant manner by factors such as visibility, metavoicing, interactivity, advice shopping, and trading affordance. Purchase intention has a favorable and large impact on trust as well. Trust mediates between visibility, metavoicing, interactivity, guidance shopping, trading affordance, and purchase intention.